2016
DOI: 10.1111/jan.13185
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to healthy eating for nurses in the workplace: an integrative review

Abstract: Reorientation of the workplace to promote healthy eating among nurses is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 66 publications
6
102
0
2
Order By: Relevance
“…Researchers ask why nurses leave (Eley et al., ; Goodare, ; Perry, Xu, et al., ), with strategies offered to help them stay in the workforce (Dawson, Stasa, Roche, Homer, & Duffield, ; Perry, Nicholls, Gallagher, & Duffield, ). Our study findings indicate that strategies need to take account of the role of culture and related social factors in workers’ health and health behaviours (Mastroianni & Storberg‐Walker, ; Nicholls et al., ). With strong underlying cultural norms that preference patient care to the detriment of nurses’ self‐care, solutions for improving bladder health and the overall health and well‐being of nurses, are unlikely to be achievable or sustainable unless they encompass cultural and social change.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Researchers ask why nurses leave (Eley et al., ; Goodare, ; Perry, Xu, et al., ), with strategies offered to help them stay in the workforce (Dawson, Stasa, Roche, Homer, & Duffield, ; Perry, Nicholls, Gallagher, & Duffield, ). Our study findings indicate that strategies need to take account of the role of culture and related social factors in workers’ health and health behaviours (Mastroianni & Storberg‐Walker, ; Nicholls et al., ). With strong underlying cultural norms that preference patient care to the detriment of nurses’ self‐care, solutions for improving bladder health and the overall health and well‐being of nurses, are unlikely to be achievable or sustainable unless they encompass cultural and social change.…”
Section: Discussionmentioning
confidence: 77%
“…With global nursing shortages and the need to maintain the health of an ageing workforce, promotion of self‐care practices in many high‐income nations is a workforce and national healthcare priority (Audit Scotland , Health Workforce Australia , National Health Service , The American Nurses Association ). Research discourse on nurses’ health has largely focussed on nurses’ individual health profiles, barriers to healthy lifestyle behaviours (diet and exercise) (Nahm et al., ; Nicholls et al., ), and reduction of occupation‐specific health risks such as work stress, long work hours, irregular meal schedules, and shift work (Kyle, Neall, & Atherton, ; Ross, Bevans, Brooks, Gibbons, & Wallen, ). Researchers ask why nurses leave (Eley et al., ; Goodare, ; Perry, Xu, et al., ), with strategies offered to help them stay in the workforce (Dawson, Stasa, Roche, Homer, & Duffield, ; Perry, Nicholls, Gallagher, & Duffield, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In promoting nutritional interventions to change the healthcare food environment, they acknowledged the central role of good nutrition for health and prevention of disease. Numerous nursing studies have identified the need to provide a healthier food environment for nurses (Nicholls et al., ). Healthier food options in cafeterias and vending machines make healthier choices easier for staff and visitors and may also highlight hospitals as industry role models: clearly necessary given the high rate of overweight and obesity in nurses as well as populations (Bogossian et al., ; Kyle, Neall, & Atherton, ).…”
Section: Discussionmentioning
confidence: 99%
“…Links have been found between smoking, alcohol abuse and the stressful nature and emotional demands of the role (Cheung & Yip, ; Han et al., ; Happell et al., ). High rates of overweight and obesity have been attributed, in part, to unhealthy eating environments and ward cultures (Nicholls, Perry, Duffield, Gallagher, & Pierce, ; Perry, Gallagher, et al., ). Low rates of leisure time physical activity are reported among time‐poor nurses, particularly those shift‐working and with home‐care responsibilities (Chin, Nam, & Lee, ; Peplonska, Bukowska, & Sobala, ).…”
Section: Introductionmentioning
confidence: 99%